Three decades of demographic trends among academic emergency physicians - Emily C. Cleveland Manchanda; Albee Y. Ling; Jason L. Bottcher; Regan H. Marsh; David F. M. Brown; Christopher L. Bennett; Maame Yaa A. B. Yiadom (Journal of the American College of Emergency Physicians Open)
Abstract Purpose To describe trends in emergency medicine faculty demographics, examining changes in the proportion of historically underrepresented groups including female, Black, and Latinx faculty over time. Methods Data from the Association of American Medical Colleges faculty roster (1990–2020) were used to assess the changing demographics of full‐time emergency medicine faculty. Descriptive statistics, graphic visualizations, and logistic regression modeling were used to illustrate trends in the proportion of female, Black, and Latinx faculty. Odds ratios (OR) were used to describe the estimated annual rate of change of underrepresented demographic groups. Results The number of full‐time emergency medicine faculty increased from 214 in 1990 to 5874 in 2020. Female emergency medicine faculty demonstrated increases in representation overall, from 35 (16.36%) in 1990 to 2247 (38.25%) in 2020, suggesting a 3% estimated annual rate of increase (OR 1.03, 95% CI 1.03–1.04) and within each academic rank. A very small positive trend was noted among Latinx faculty (n = 3, 1.40% in 1990 to n = 326, 5.55% in 2020; OR 1.01, 95% CI 1.01–1.02), whereas an even smaller, statistically insignificant increase was observed among Black emergency medicine faculty during the 31‐year study period (N = 9, 4.21% in 1990 and N = 266, 4.53% in 2020; OR 1.00, 95% CI 0.99–1.00). Conclusions Although female physicians have progressed toward equitable representation among academic emergency medicine faculty, no meaningful progress has been made toward racial parity. The persistent underrepresentation of Black and Latinx physicians in the academic emergency medicine workforce underscores the need for urgent structural changes to address contemporary manifestations of racism in academic medicine and beyond.